2013 ACM / IEEE International Symposium on Empirical Software Engineering and Measurement 2013
DOI: 10.1109/esem.2013.28
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Barriers to the Systematic Literature Review Process

Abstract: Conducting a systematic literature review (SLR) is difficult and time-consuming for an experienced researcher, and even more so for a novice graduate student. With a better understanding of the most common difficulties in the SLR process, mentors will be better prepared to guide novices through the process. This understanding will help researchers have more realistic expectations of the SLR process and will help mentors guide novices through its planning, execution, and documentation phases. Consequently, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
56
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 14 publications
3
56
0
6
Order By: Relevance
“…Knowledge intensiveness, tediousness and errorproneness are the key factors cited for low adoption of SR in SE. Several tertiary reviews [24,1,7,8,10] are congruent with these observations.…”
Section: Introductionsupporting
confidence: 70%
“…Knowledge intensiveness, tediousness and errorproneness are the key factors cited for low adoption of SR in SE. Several tertiary reviews [24,1,7,8,10] are congruent with these observations.…”
Section: Introductionsupporting
confidence: 70%
“…Only one tool, SLR-Tool, assisted this stage effectively. In addition, support for the search process (a frequently stressed issue within the community [5,6,7,8]), is largely absent. SLRTOOL is the only tool that provides an internal search facility (i.e.…”
Section: Discussion Of Resultsmentioning
confidence: 97%
“…Despite having a well-defined process, SRs are quite labour intensive and error prone [5,6,7,8] making them prime candidates for automated support. A number of tools to support the SR process were identified through a recent mapping study which found a predominance of visualisation and text mining techniques to support study selection, data extraction and data synthesis [9].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work (described in more detail in Section 2.2) [2], we identified barriers that hinder the SLR process. Based on our analysis of data from three sources: (1) our own experiences conducting SLRs, (2) a graduatelevel course on SLRs, and (3) a survey of authors of SLRs published in SE venues, we identified the aspects of the SLR process that were most difficult, most time-consuming, and most in need of tool support.…”
Section: Introductionmentioning
confidence: 99%